HISTORIOGRAPHY OF RELATIONS BETWEEN UZBEKISTAN AND AZERBAIJAN (1945-1991) - Adilov Farkhod Abduvalievich (Web of Journals Publishing, 2025)
This article provides information about the research work carried out on the issue of the historiography of the relations between Uzbekistan and Azerbaijan.
Keywords: history, research, spiritual and cultural, independence, Soviet, culture, people, society, ideology and spirituality, document, material, periodicals, memories and recollections, oral history.